Effects of extractum cepae, heparin, allantoin gel and silver sulfadiazine on burn wound healing: an experimental study in a rat model - Durmus, A. S.; Yaman, M.; Can, H. N. (Czech Academy Agricultural Sciences, 2012)
These experiments were conducted in order to compare the effects of extractum cepae, heparin, allantoin gel (CTBX) and silver sulfadiazine (SSD) cream on burn wound healing in rats. Thirty six adult, female Wistar albino rats were divided into three equal groups. A burn was made on the back of all rats. The burned areas in the first, second and third groups were covered with cold cream (control), SSD skin cream and CTBX twice a day, respectively. Seven and 14 days later, the rats were sacrificed and burned skin tissue samples were collected from the rats for histopathological examinations. Histopatological evaluations on the 7th and 14th days showed burn healing to be better in the CTBX and SSD groups with respect to the control group. The best burn wound healing was observed in the CTBX group (P < 0.001). Wound healing was significantly different between the groups at days 7 and 14 (P < 0.001). In conclusion, application of CTBX has significant positive effects on the healing of burn wounds in a rat model.
Keywords: extractum cepae; heparin; allantoin; silver sulfadiazine; burn; rat